The Use Of Picture Files To Enhance The Seventh Grade Students’ Participation And Vocabulary Achievement - Femdana Erlitasari (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This Classroom Action Research was conducted to enhance the seventh grade students’ participation and vocabulary achievement by using picture files at SMP Al-Muttaqin Jember. Based on the preliminary study done by the researcher, the English teacher revealed that most of the seventh grade students faced some difficulties in mastering English words. They got difficulty in memorizing new words, understanding the word meanings, and they were still passive during the teaching and learning process. Referring to the problems above, one possible way to anticipate such an issue in vocabulary learning is through the use of picture files. This research was carried out in two cycles. Each cycle was done in three meetings. Two meetings for the action and one meeting for the vocabulary achievement test. This research covered four stages of activities namely: (1) the planning of the action, (2) the implementation of the action, (3) observation and evaluation, (4) data analysis and reflection of the action. The result of the observation showed that in the first meeting of Cycle 1, there were 21 students or 65.6% of 32 students who categorized as an active student and there were 22 students or 68.7% of 32 students who actively involved in teaching learning process in the second meeting. Thus, the average result of the students’ participation in Cycle 1 was 67.1%. Meanwhile, the result of the vocabulary achievement test in Cycle 1 showed that there were only 20 students or 62.5% of 32 students who got at least ≥70. It meant that the results of the observation and the actions given in Cycle 1 had not fulfilled the successful criteria of this research. The result of Cycle 2 showed an improvement on the students’ participation and vocabulary achievement. Based on the observation in Cycle 2, it was found that there were 24 students or 75% of students who were involved in the first meting and there were 25 students or 78.1% of students who actively involved in teaching learning process in the second meeting. The average of the students’ participation in Cycle 2 was 76.5%. It can be said that the result of the observation was increased from 67.1% in Cycle 1 to 76.5% in Cycle 2. Then, the result of the students’ vocabulary achievement test in Cycle 2 showed that the percentage of the students who got at least 70 was 78.1%, it was improved from 62.5% in Cycle 1 to 78.1% in Cycle 2. Based on the results above, it could be concluded that the success criteria of this research had been achieved in Cycle 2. It proved that the use picture files could enhance the seventh grade students’ participation and vocabulary achievement at SMP Al-Muttaqin Jember.
Reupload Repositori File 13 April 2026_Kholif Basri
Keywords: Classroom; participation; and vocabulary